Rebuttal from Dr. Dettlaff - Dettlaff, Alan J. (Families in society, 2025)
In “Counterpoint: Child Welfare System: Evolution/Revolution,” Dr. Jessica Pryce responded to my article, “Point: Abolition of the Child Welfare System: An Invitation,” by offering an alternative to abolition, proposing a blend of reformative and transformative reforms. In this response, I highlight two foundational differences in our views that, I believe, distinguish our approaches to the child welfare system: First, our understanding of the system’s origins and intent, and second, our understanding of the role of reforms. These differences also underscore a broader distinction in how we view the role of the state in the lives of children, families, and communities.